A regulatory SNP causes a human genetic disease by creating a new transcriptional promoter. - De Gobbi, M; Viprakasit, V; Hughes, J; Fisher, C; Buckle, V; Ayyub, H; Gibbons, R; Vernimmen, D; Yoshinaga, Y; de Jong, P; Cheng, J; Rubin, E; et al. (2006)
We describe a pathogenetic mechanism underlying a variant form of the inherited blood disorder alpha thalassemia. Association studies of affected individuals from Melanesia localized the disease trait to the telomeric region of human chromosome 16, which includes the alpha-globin gene cluster, but no molecular defects were detected by conventional approaches. After resequencing and using a combination of chromatin immunoprecipitation and expression analysis on a tiled oligonucleotide array, we identified a gain-of-function regulatory single-nucleotide polymorphism (rSNP) in a nongenic region between the alpha-globin genes and their upstream regulatory elements. The rSNP creates a new promoterlike element that interferes with normal activation of all downstream alpha-like globin genes. Thus, our work illustrates a strategy for distinguishing between neutral and functionally important rSNPs, and it also identifies a pathogenetic mechanism that could potentially underlie other genetic diseases.